2018
DOI: 10.37358/rc.18.2.6120
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of CD8, CDX2, P53, D2-40 and KI 67 in Colorectal Adenocarcinoma, Conventional and Malignant Colo-rectal Polyps

Abstract: 82 patients, who had been diagnosed with colo-rectal adenocarcinoma in our department between 2007 and 2014, were included in our study. Additionally, 31 patients with colo-rectal polyps (20 conventional adenomatous polyps and 11 malignant colo-rectal polyps) were also included in this study. The patients with colo-rectal adenocarcinoma were reevaluated in terms of gender, age, topography of recto-colic tumor, TNM stadialization, vasculo-lymphatic invasion, lymph nodes metastases and distant metastases. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A number of studies have revealed the correlation between QT prolongation and severity of arrhythmic risk in patient with chronic hepatic disease [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Table 2 revealed us that the frequency of arrhythmic events ( premature atrial contraction and atrial fibrillation) is much higher in patients with QT prolongation than in patients It has been reported that QT prolongation can lead to torsades de pointes, a life-threateningabnormal heart rhythm [18].We explored the correlation found between the length of QT interval and the biological and the biochemical parameters, which can lead to possible prolongation of QT interval (table 4).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have revealed the correlation between QT prolongation and severity of arrhythmic risk in patient with chronic hepatic disease [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Table 2 revealed us that the frequency of arrhythmic events ( premature atrial contraction and atrial fibrillation) is much higher in patients with QT prolongation than in patients It has been reported that QT prolongation can lead to torsades de pointes, a life-threateningabnormal heart rhythm [18].We explored the correlation found between the length of QT interval and the biological and the biochemical parameters, which can lead to possible prolongation of QT interval (table 4).…”
Section: Resultsmentioning
confidence: 99%
“…But the pediatrician with expertise in diabetes, the diabetes nursing educator, the dietitian, and the mental health expert needs to be involved in managing this disease as well. All these professions should contribute to the proper education of both the children and adolescents with type 1 diabetes and also their caregivers [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Non-tumor colonic mucosa tissues, adenomas and colon adenocarcinomas were analyzed to evaluate the expression of the COX2 and Osteopontin biomarkers in relation to proliferative activity using Ki-67, a monoclonal antibody directed at a nuclear antigen expressed in proliferating cells (21). As described by several studies, a high cell proliferation index was found in all cases of colon adenocarcinoma (20,(22)(23)(24); while in the adenomas the distribution pattern for Ki-67 showed expression beyond the crypt bases, similar to previously reported by Torlakovic et. al.…”
Section: Discussiónmentioning
confidence: 99%